Short-Term Effects on Tear Film Following Cosmetic Botulinum Toxin Injections in Healthy Individuals - Sandia Bhojwani, Naveed Ahmad Khan, Sarfraz Ahmad, Asadullah Awan, Masroor Ahmad Baloch, Sadaffasih, Zill-E-Huma Tariq, Fahim Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The cosmetic treatment Botox relies on the paralysis of facial muscles in order to minimize wrinkles. Research now focuses on investigating how Botox treatment influences the tear film at the same time it reduces facial wrinkles. Objective: To evaluate the short-term effects of cosmetic botulinum toxin injections on the tear film in healthy individuals, with a focus on tear production, stability, and overall ocular health. Methodology: This prospective cohort study was conducted at Burn and Plastic Surgery Center Hayatabad, Peshawar during March 2022 to June 2023 involving 85 healthy individuals who were selected based on their decision to undergo cosmetic botulinum toxin injections for aesthetic purposes. Results: A total of 85 participants were added with mean age 30.5 ± 5.7 years. 47% males (40 participants) and 53% females (45 participants). The mean tear production was 12.4 ± 3.5 mm, and the mean tear breakup time (TBUT) was 10.3 ± 2.1 seconds. Only 8% of participants reported any discomfort at baseline. At baseline, only 8% of participants reported ocular discomfort, but this increased significantly to 23% 1-week post-injection (p < 0.05). By 1-month post-injection, the discomfort decreased to 9%, which was not statistically significant (p > 0.05). Conclusion: Cosmetic botulinum toxin injections have a short-term impact on tear film stability and tear production, with a gradual recovery within a month. These findings highlight the need for careful assessment of ocular health in individuals undergoing botulinum toxin treatments, especially those with underlying dry eye conditions or concerns about tear production. Keywords: Botulinum toxin, tear film, tear production, Schirmer’s test, tear breakup time, ocular discomfort, visual disturbances.